LTP 53/35 paraffin as a potential phase change material - Ksionek, Dariusz (Instal, 2021)
The article contains an analysis of potential to heat storage of paraffin LTP 53/35 Polwax production. For this study one of the thermal analysis methods was used – Differential Scanning Calorimetry (DSC) which is frequently used to study phase change materials. The potential to heat accumulation of the investigated paraffin has been determined in comparison to heat storage potential of water, which is widely used in heat and cold storage.